Work Discipline, Teamwork, Communication's Impact on Employee Performance CV. Golden Harvest - Nanda, Marta Dwi; Sulistyorini, Sulistyorini; Mulyantomo, Edy (Economics and Business Solutions Journal, 2025)
Examining the effects of communication, teamwork, and work discipline on employee performance at CV Golden Harvest is the aim of this study. Organizational success depends on employee performance, and human resources are crucial to achieving corporate goals. 36 employees participated in this study, which used a quantitative methodology and survey questionnaires. SPSS 22.0 was used for data processing in order to examine each variable's partial and simultaneous influence. The findings show that employee performance is significantly and favorably impacted by teamwork, communication, and work discipline. However, the results of individual analysis vary work discipline has a positive but insignificant effect on performance, communication has a negative and negligible effect, and cooperation has a positive and significant impact. While good teamwork fosters synergy among people, good work discipline can improve adherence to business policies. Conversely, good communication is essential for enhancing professional relationships and reducing miscommunications. These results give management information to help them develop plans to enhance worker performance by managing communication, teamwork, and work discipline.